Economic Analysis of Zero Tillage Technology in Maize - V. Rajendra Prasad,; M . Goverdhan, (Journal of Agricultural Extension Management, 2025)
Farmers of Neelaigudem village in Tripuraram mandal in Nalgonda district like all other farmers of NSP left canal command area are habituated to Rice-Rice Monoculture. In recent years they are facing the problem of late release of canal water in Kharif, consequent outbreak of pest and diseases, advancement of Rabi towards summer, with enhanced load of pest and diseases ultimately resulting in drastic yield reduction. The preponderance of low minimum support price has put a question mark on Rabi rice cultivation in the area. At last, they came across maize crop introduced by the Agricultural Research Station, Kampasagar under the ATMA project assisted by the State Department of Agriculture. They have been given seeds, weedicide and fertilizers on 100 per cent subsidy from ATMA and the research station was instrumental in introducing zero tillage machines for sowing operation immediately after harvesting of kharif paddy without going for hefty land preparation for sowing. A tractor drawn zero till drum to meet the farmers demand in the surrounding area of the Research Station to grow maize under zero till drill conditions was also introduced. Zero till drum enables making of holes in the unprepared harvested rice field thus facilitating women labour for proper seed placement. Further, zero till drill machine is seed-cum-ferti type. In the first crop season (2006-07), only two farmers came forward to grow maize in Rabi after rice under zero tillage method. In the subsequent year, the farmers have realized the advantage of growing maize under zero tillage condition, which resulted in cultivation of 200 acres of maize in the village which is commendable. The main advantage of the technology is saving of the cost of Rs. 2500/- per acre towards land preparation. The crop season .is advanced by at least 20 days to avoid coincidence of peak summer at harvesting phase